The Influence of Capital Structure, Profitability, and Operating Costs on Corporate Income Tax in Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2019–2022 - Sari, Nabila Famutia; Sidik, M. Muhayin A.; Asliana, Endang (Majapahit Journal of Islamic Finance and Management, 2025)
This research explores the relationship between a company’s financial structure, profit performance, and operational spending on the calculation of corporate income tax in Indonesian consumer goods firms listed on the IDX from 2019 to 2022. The study arises from the sector’s economic importance and the inconsistent outcomes reported in earlier research. Adopting a quantitative framework, the analysis uses secondary data from the annual financial statements of 33 firms and applies descriptive statistics, tests of classical assumptions, and multiple regression analysis (including t-test, F-test, and R²) through SPSS. The results indicate that while leverage (DER) does not significantly affect corporate tax, both profitability metrics (ROA and NPM) and operating expenses have a clear positive impact. This implies that increases in profits and operational costs lead to higher tax obligations, whereas debt levels have minimal influence. The study advises that businesses carefully balance profitability and cost management to enhance tax efficiency while sustaining overall financial health.